FAILURE ANALYSIS OF THE FLOUR PRESS MACHINE AND ALTERNATIVE SOLUTIONS AT PT ANEKA USAHA LABA JAYA UTAMA PESAWARAN - Gusri Akhyar Ibrahim; Arinal Hamni; Yanuar Burhanuddin; Achmad Yahya Teguh Panuju; Sahid Ar Rafi; Rizki Ramadhan (Asosiasi Peneliti Sriwijaya, 2022)
Processing chocolate from dried cocoa beans to become a ready-to-eat chocolate paste involves a long process, including separating the cocoa oil from the flour. The separation process is mechanized using a press machine with high pressure at a certain temperature level. However, a press machine deals with obstacles prone to failure and damage. This study aims to analyze the causes of the chocolate pressing machine's failure using hydraulic pressure and find alternative repair solutions. The cylinder of the machine press is made of stainless steel material and has a cylindrical geometry with a diameter of 23 mm and a tube length of 30 cm. Failure analysis is carried out by observing the machine's operating conditions, the procedure for its use, and the load imposed on the machine, including, in this case, the service life to date. Observations were also made on the form of failure, the type of damage, and each component's function. Thus, based on the data obtained and relates to the theoretical theory, the conditions that should occur are obtained. The study results showed that the damages occurred, such as press tube damage, deformed fins, clogged gaps between fins, worn support rods, corroded threads, worn and stiff seals, and bearing damage to rupture. More damage was caused by the tilted position of the machine so that it didn't move the flashlight anymore. The part of the machine must be repaired flat based on standard procedures operation and carry out periodic checks on machine components.